EFFECTS OF RIBOFLAV1N SUPPLEMENTATION ON THE TERATOGENIC EFFECTS OF SODIUM BORATE IN WHITE RATS - Tri Wahyu Pangestiningsih; Sumiyati Sunaryo (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 1995)
Na-borate gave teratogenic effects both to rats and chickens. In chickens the fetal malformations caused by borate treatments were similar to those due to riboflavin deficiency. It was proposed that in embryonated eggs borate built a bond with riboflavin, so that riboflavin could not junction properly. This present investigation was conducted to assess the possibility of riboflavin in prevent the teratogenic effects of Na-borate in rats.Nineteen primigravida Wistar rats were allocated randomly to one of treatment groups, i. e, 9 rats were orally treated with 180 mg/200g BW/day, No-borate the other 10 rats beside treated with Na-borate, they were also treated orally with 2.5 mg/rat/day riboflavin. The treatments were done during the pregnancy on day 6 to 15. On day 20 the pregnant does were caesarean sectioned under ether anaesthesia. After all fetal malformations were noted, then all fetuses were placed in alcohol 70%, prepared for alizarin method for microscopic skeleton inspection. Chi square analysis of the gross inspection malformations, i e. the resorbed vs. the unresorbed, the alive vs. the dead, the haemorrhage vs. the non Hemorrhage fetuses of the two treatments showed unsignificant difference. Riboflavin supplementation increased singnificantly the number of fetuses with omphalocel. T-test analysis indicated that riboflavinsupplementation highly significantly caused the fore and hind paw, costal, sternal defects became more serious, if also significantly reduced the weight and the length of the fetuses. This investigation revealed that riboflavin supplementation failed to prevent, but even caused the teratogenic effects of the Na-borate to rats became more serious.